Flood-Controlled Excess-Air Formation Favors Aerobic Respiration and Limits Denitrification Activity in Riparian Groundwater - Peter, Simone; Mächler, Lars; Kipfer, Rolf; Wehrli, Bernhard; Durisch-Kaiser, Edith (Frontiers in Environmental Science, 2015)
The saturated riparian zones of rivers act as spatially and temporally variable biogeochemical reactors. This complicates the assessment of biogeochemical transport and transformation processes. During a flood event, excess-air formation, i.e. the inclusion and dissolution of air bubbles into groundwater, can introduce high amounts of dissolved O2 and thereby affect biogeochemical processes in groundwater. With the help of a field-installed membrane-inlet mass-spectrometer we resolved the effects of flood induced excess-air formationon organic carbon and nitrogen transformations in groundwater of different riparian zones of a restored section of the River Thur, Switzerland. The results show that the flood event triggered high aerobic respiration activity in the groundwater below a zone densely populated with willow plants. The flood introduced high concentrations of O2 (230 µmol L–1) to the groundwater through the formation of excess air and transported up to 400 µmol L 1 organic carbon from the soil/root layer into groundwater during the movement of the water table. A rapid respiration process, quantified via the measurements of O2, CO2 and noble-gas concentrations, led to fast depletion of the introduced O2 and organic carbon and to high CO2 concentration (590 µmol L–1) in the groundwater shortly after the flood. The synchronous analysis of different nitrogen species allowed studying the importance of denitrification activity. The results indicate that in the willow zone excess-air formation inhibited denitrification through high O2 concentration input. Instead, the observed decrease in nitrate concentration ( 50 µmol N L 1) may be related to fostered nitrate uptake by plants. In the other riparian zones closer to the river, no significant excess-air formation and corresponding respiration activity was observed. Overall, analyzing the dissolved gases in the groundwater significantly contributed to deciphering biogeochemical processes in the riparian aquifer characterized by pronounced changes in the flow regime and by spatial heterogeneity of the vegetation. Measuring excess-air formation helped identifying and explaining the low denitrification activity in a zone with high organic carbon turnover and to quantify organic carbon sources.